Use of Medicare's Diabetes Self-Management Training Benefit. (August 2015) - Strawbridge, Larisa M.; Lloyd, Jennifer T.; Meadow, Ann; Riley, Gerald F.; Howell, Benjamin L.
Medicare began reimbursing for outpatient diabetes self-management training (DSMT) in 2000; however, little is known about program utilization. Individuals diagnosed with diabetes in 2010 were identified from a 20% random selection of the Medicare fee-for-service population ( N = 110, 064). Medicare administrative and claims files were used to determine DSMT utilization. Multivariate logistic regression analyses evaluated the association of demographic, health status, and provider availability factors with DSMT utilization. Approximately 5% of Medicare beneficiaries with newly diagnosed diabetes used DSMT services. The adjusted odds of any utilization were lower among men compared with women, older individuals compared with younger, non-Whites compared with Whites, people dually eligible for Medicare and Medicaid compared with nondual eligibles, and patients with comorbidities compared with individuals without those conditions. Additionally, the adjusted odds of utilizing DSMT increased as the availability of providers who offered DSMT services increased and varied by Census region. Utilization of DSMT among Medicare beneficiaries with newly diagnosed diabetes is low. There appear to be marked disparities in access to DSMT by demographic and health status factors and availability of DSMT providers. In light of the increasing prevalence of diabetes, future research should identify barriers to DSMT access, describe DSMT providers, and explore the impact of DSMT services. With preventive services being increasingly covered by insurers, the low utilization of DSMT, a preventive service benefit that has existed for almost 15 years, highlights the challenges that may be encountered to achieve widespread dissemination and uptake of the new services.